Transparency and Prevention of Corruption: Reanalysis of General Perceptions of Budget Transparency in the Batang Regency Government - Dina Fadiyah; Sapto Setyo Nugroho (JIP (Jurnal Ilmu Pemerintahan) : Kajian Ilmu Pemerintahan dan Politik Daerah, 2023)
This paper reviews the results of research that examines the relevance of the concepts and practices of budget transparency and the concepts and practices of good and clean government. This paper re-analyzes the data on general perceptions of budget transparency in the Batang Regency Government in 2012-2017 with existing general data in 2022. The results of the re-analysis show that general perceptions are more or less the same between pre-2017 and post-2017 can be reviewed by there is an explanation of the leadership context, implementation context, and strategic context.